If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x=-27+70
We move all terms to the left:
3x-(-27+70)=0
We add all the numbers together, and all the variables
3x-43=0
We move all terms containing x to the left, all other terms to the right
3x=43
x=43/3
x=14+1/3
| x²+10x-144=0 | | 2x+20=5x+6 | | 142=2x2 | | 18-2(7x-2)= | | 11+6x-14=3/4(15x-5) | | 2/3.25=x/6.5 | | 2x+2(3)=2 | | 3x+5=37.5 | | 2x+2(3)=3 | | -4.9t^2+102t+100=0 | | 3x+3=15+5x | | x=16=16+16+2x-3x | | 8(((2x+5)/5)+x-3)=61 | | 4x-6=2x+40 | | 90+90+(2x+4)+(3x-29)=306 | | 90+90+(2x+4)+(3x-29)=36 | | 0.554x+2=6.05 | | X^2-14x-83=4 | | .5x+12=2x+27 | | 7/4=-5x | | 6a+7(6)=a-2 | | -3z=8-2 | | 0.48x-1.52=-506 | | 2x+5=37.5 | | 42=4x^2 | | x+5=37.5 | | -226=-12x+2 | | 19=x-(-8) | | 6/x=1,7 | | 15+x=71 | | 2=-12x+2 | | -7x-2=3x+10 |